Penyisihan Nh3 Pada Grey Water Dengan Menggunakan Sequencing Batch Biofilm Reactor - Kiki Ramadanti; Shinta Elystia; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Domestic wastewater based on its characteristics is divided into two type which is black water and grey water. Grey water that directly flowed into the environment is one of the main causes of water pollution. The high content of organic matter causes grey water must be treated. Microorganisms can be use to treat this grey water one of them is microalgae Chlorella sp which consume organic matter as a source of nutrients for its growth. In this study, the addition of the Kaldness 1 (K1) biocarrier as a medium for attaching microorganisms were performed on the Sequencing Batch Biofilm Reactor (SBBR) process. Microalgae Chlorella sp. grown as suspended in grey water and attached to Kaldness 1 (K1). This study aims to examine ammonia parameters in grey water. Variations that use in this treatment are reaction times of 60, 90 and 120 minutes and media filling volumes of 0, 20, 40 and 60%. The best results for ammonia removal was 83% in a reactor filled with 20% Kaldness 1 as biocarrier and a reaction time of 120 minutes.Keywords: SBBR, Biocarrier Kaldness 1, Chlorella sp., Grey Water.